Uji Aktivitas Antibakteri Ekstrak Etanol Kulit Kayu Laban (Vitex pubescens Vahl) terhadap bakteri Escherichia coli - Talitha Cresentia Rahma; Dyan Fitri Nugraha (Jurnal Pelayanan Kefarmasian dan Sains, 2020)
Background: In the world, 800.000 children die every year due to diarrheal diseases. Chronic diarrhea is usually caused by a bacterial infection, one of which is E. coli. Empirically, Dayaknese in Sampit, Central Kalimantan consuming Laban bark to treat diarrhea and dysentery. Through this research, people get scientific information about Laban wood as an alternative herbal medicine for treating diarrhea. Objective: To find out whether Laban bark can inhibit Escherichia coli bacteria and to determine the minimum inhibitory concentration in Laban bark extract that can inhibit Escherichia coli bacteria. Methods: This type of research used true experimental design with research post test only control group design. The research subjects were Escherichia coli cultured on Muller Hinton Agar (MHA) media and Laban bark extract with 3 different concentrations using the disc diffusion method. This study had 2 control groups and 3 treatment groups, DMSO as negative control, ciprofloxacin as positive control and ethanol extract of Laban bark with concentrations of 25%, 50%, and 75%. Inhibition zone diameter results were analyzed quantitatively in 3 replications. Results: The results showed that the concentrations of 25%, 50% and 75% of the extract had bacterial inhibition, in the very strong antibacterial category. Conclusion: The ethanol extract of Laban bark can inhibit the growth of Escherichia coli with an minimun inhibitory concentration 25%, which is in the very strong inhibition category. Keywords: Disc diffusion, Escherichia coli, Laban bark (Vitex pubescens Vahl)